2017
DOI: 10.11113/sh.v9n3-2.1271
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Online Privacy Concern as a Mediator between Internet Self-Efficacy and Online Technical Protection Privacy Behavior

Abstract: Online risks may result in unnecessary harm but these risks can be minimized by being online privacy concerned and by taking privacy protective actions. Few studies examined the impact of privacy concern and internet self-efficacy on the online technical protection privacy behavior. Therefore, this research aims to investigate the effect of privacy concern and internet self-efficacy on technical protection. Quantitative and purposive sampling methods were used in this study. Data were gathered via questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
1
0
3
Order By: Relevance
“…It is noteworthy that privacy concerns not only directly influenced the privacy protection behavior of the youths but also functioned as an indirect factor between the relationships of perceived threat, self-efficacy, response efficacy, and privacy protection behavior. This finding is in line with the study of Lee et al ( 2017 ). They suggest that privacy concerns have a positive impact on online privacy protection behavior among young people, which means that privacy concerns are an important element of privacy management for youth that cannot be ignored.…”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that privacy concerns not only directly influenced the privacy protection behavior of the youths but also functioned as an indirect factor between the relationships of perceived threat, self-efficacy, response efficacy, and privacy protection behavior. This finding is in line with the study of Lee et al ( 2017 ). They suggest that privacy concerns have a positive impact on online privacy protection behavior among young people, which means that privacy concerns are an important element of privacy management for youth that cannot be ignored.…”
Section: Discussionsupporting
confidence: 94%
“…Privacy concern is recognized as a significant factor in explaining online privacy behavior (Choi et al, 2018), and therefore, this study investigates it as a potential mediating variable. As mentioned earlier, subjective privacy literacy is often linked with privacy self-efficacy, and previous research has found that self-efficacy enhances privacy concern (Mohamed and Ahmad, 2012;Lee et al, 2017), suggesting a positive correlation between subjective privacy literacy and privacy concern. In terms of objective privacy literacy, research has confirmed its positive effect on privacy concern.…”
Section: Mediating Role Of Privacy Concernmentioning
confidence: 68%
“…La facilidad en el acceso a las redes sociales ha traído consigo condiciones no favorables que ponen en riesgo a los adolescentes; por ejemplo, se puede acceder a redes sociales e internet sin una debida supervisión, no se verifica la identidad de la persona al crear una cuenta, y se añaden amigos al perfil sin necesidad de tener una interacción cara a cara (Espinar & González, 2009). Existe una ausencia de monitorización de los menores por sus padres, una falta de información acerca de las condiciones de uso y privacidad de las diferentes redes sociales, y una potencial complicación al producirse una adicción a este tipo de aplicaciones (Lee et al, 2017).…”
Section: Introductionunclassified
“…Otro factor asociado es la autoeficacia en el uso de internet (Lee et al, 2017): quienes presentan deficiencias en el conocimiento y manejo de internet se perciben como menos autoeficaces para proteger sus datos y privacidad, mientras que aquellos que se muestran confiados en sus habilidades en internet tienden a ser más autoeficaces en el manejo de su privacidad y datos. Es por ello que es de gran importancia que los jóvenes tengan conocimientos necesarios sobre el uso de redes sociales y sobre la navegación en sitios web, pues cuanto más informados estén mejor podrán proteger sus datos y privacidad.…”
Section: Introductionunclassified
See 1 more Smart Citation